2007
DOI: 10.1097/mpa.0b013e3180a6f366
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effects of Noniodinized and Iodinized Ionic Contrast Media and Gadoteric Acid in Acute Necrotizing Pancreatitis

Abstract: Ionic and nonionic contrast media and gadoteric acid did not produce adverse effects in the present model of acute necrotizing pancreatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
2
0
2
Order By: Relevance
“…In a report on a rat model of cerulean-induced pancreatitis, the injection of contrast seemed to increase the rates of pancreatic necrosis and mortality [ 6 ]. However in a taurocholate-induced model of experimental pancreatitis, the authors have suggested that neither ionic nor non-ionic contrasts increase pancreatic necrosis [ 16 ]. Recent clinical studies have shown that early CT does not aggravate AP and, on the contrary, provides important prognostic information [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a report on a rat model of cerulean-induced pancreatitis, the injection of contrast seemed to increase the rates of pancreatic necrosis and mortality [ 6 ]. However in a taurocholate-induced model of experimental pancreatitis, the authors have suggested that neither ionic nor non-ionic contrasts increase pancreatic necrosis [ 16 ]. Recent clinical studies have shown that early CT does not aggravate AP and, on the contrary, provides important prognostic information [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among these bile salts, the taurine‐conjugated bile salt Na‐TC is the most widely used and best characterized to date in inducing AP. The Na‐TC ductal infusion model has been shown to induce pancreatic oedema, haemorrhage and necrosis in large animals, such as rabbits, 62 swans, 63 dogs 64 and pigs 65,66 . However, the pancreatic injury in these large animals is not sufficient to produce multiple organ dysfunction syndromes (MODS).…”
Section: Induction Of Ap By Bile Saltsmentioning
confidence: 99%
“…Cerca de um terço dos entrevistados realizam a TC na admissão destes doentes. Discutem-se os problemas relacionados à utilização de contraste na PA, que poderia transformar uma PA leve em necrótica 14 . O fator custo também deve ser considerado, além do fato de que o principal fator local que influencia o prognóstico de um doente com PA é a necrose, que só pode ser vista na TC a partir do terceiro dia do início do surto e idealmente a partir do quinto dia 15 .…”
Section: Emprego De Antibióticos Na Pancreatite Agudaunclassified